Saying goodbye to monotypy in the poorly known genus Austrophyto Lopes, 1989 (Diptera: Sarcophagidae): new diagnosis and description of two new species - Mulieri, Pablo Ricardo (Zootaxa, 2017)
The Argentinean endemic genus Austrophyto Lopes, 1989 is revised. The diagnosis of the genus is revised and circumscribed, especially focusing on the configuration of the male terminalia. The male of Austrophyto cordobensis is redescribed and two new species, A. noa sp. nov. and A. mariluisi sp. nov., are described. Structures of the male terminalia of all species are documented and compared. A key to the adult males of the species is presented. The genus Austrophyto Lopes is now represented by three species distributed in north-western Argentina.